Aplikasi Pupuk Area dan Pupuk Kandang Kambing Untuk Meningkatkan N total Tanah pada Inceptisol Kwala Bekala dan Kaitannya Trhadap Pertumbuhan Jagung (Zea mays L.) - Arfan Dwi Putra; MMB Damanik; Hamidan Hanum (Jurnal Agroekoteknologi, 2015)
This aims of research was study about the effect of application of urea fertilizer and goat manure toimprove N-total on Inceptisol Kwala Bekala and its relation to the growth of maize. The researchwas conducted in the screen house and Chemical and Soil Fertility Laboratory, Faculty ofAgriculture, University of North Sumatra .This study used randomized block designed whichconsists of 2 factors and 3 replications. The first factor urea which consists of 4 levels : 1. U0 (0kg/ha), 2. U1 (100 kg/ha), 3. U2 (200 kg/ha), 4. U3 (300 kg/ha) and the second factor of goatmanure: 1. K0 (0 tons/ha), 2. K1 (10 tons/ha), 3. K2 (20 tons/ha), 4. K3 (30 tons/ha).The resultsshowed urea fertilizer application increased significantly of plant height, the best treatment at 100kg/ha. Application of goat manure increased significantly soil C-organic, N-uptake, plant height,dry weight and dry root plant, the best treatment at 30 tons/ha. Interaction of urea fertilizerapplication and goat manure increased the dry weight of shoot and N-uptake. The best treatmentwas the application 100 kg/ha urea and goat manure 30 tons/ha.Keywords : urea fertilizer , goat manure , N-total.